Studi Optimasi Kinerja Sucker Rod Pump Pada Sumur A-1, A-2,Z-1, Dan Z-2 Menggunakan Perangkat Lunak Prosper - Syahrinal Faiz; Djoko Sulistyanto; Samso ST (Lembaga Penelitian Universitas Trisakti, 2015)
Sucker rod pump is a type of artificial lift methods are often used to date. Sucker rod pump suitablefor wells with low productivity, as well as the relative ease in operation and treatment becausepeople in the field have been much acquainted with this type of pump. Sucker rod pump workingprinciple or often called beam pumping up and down movement harnesses from the plunger topush the fluid reservoir to the surface. Optimization sucker rod pump performance can beperformed using software prosper.